Studies on Growth, Yield Attributes, Yield and Economics of Lathyrus in Rice Fallow under Various Tillage Systems and Foliar Spray of Nutrients in Red and Lateritic Soils - Biswas, Sumana; Akhil, K.; Patre, Siddharth Shankar; Barik, Arun Kumar (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted during rabi seasons (November to March) of 2022–23 and 2023–24 at Agricultural farm of Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, Birbhum, West Bengal, India to find out the effect of various tillage systems and foliar spray of nutrients on growth, yield attributes, yield and economics of lathyrus in rice fallow. The experiment was laid out in split plot design replicated thrice having two tillage practices (zero tillage and conventional tillage) in main plots and six levels of foliar spray of nutrients in sub-plots. Various tillage practices had on significant response on growth and yield attributes of lathyrus. Among different tillage practices, significant response with highest seed yield (1311.5 kg ha-1), stover yield (1584.4 kg ha-1) and gross return (74101 Rs. ha-1) was received under conventional tillage but return per rupee investment was recorded highest on Zero tillage (2.73 Rs. ha-1). Foliar spray of nutrients had significant response on various growth parameters, yield attributes, yield (seed, stover and biological) and economic returns except harvest index of lathyrus. Foliar spray with N: P: K (19:19:19) @ 2% at 30 DAS and 45 DAS+ZnSO4 @ 0.5% at 40 DAS+Boron (20%) @ 0.1% at 50 DAS registered significantly highest seed yield (1432.1 kg ha-1), stover yield (1691.8 kg ha-1) and gross return, net return and return rupee-1 investment (80915 Rs. ha-1, 53125 Rs. ha-1, 2.91 ` ha-1, respectively) among different foliar spray of nutrients.